Tinjauan Yuridis Terhadap Perlindungan Anak Pasca Perceraian Orang Tua - Herdy Pratama Susantyo; Wahibatul Maghfuroh (Policy and Law Journal, 2025)
Islam places harmony within the family as a fundamental aspect, viewing marriage as a sacred bond aimed at creating a prosperous family. However, divorce remains an unavoidable social reality, although in Islam, it is only permitted as a last resort. One of the most significant impacts of divorce is on children, who may experience emotional and psychological instability, as well as challenges in their social and academic lives. Therefore, it is the responsibility of parents to minimise the negative effects of divorce on their children. From a legal perspective, divorce affects the rights and obligations of parents, particularly regarding custody and child support. In the Indonesian legal system, various regulations such as Law No. 1 of 1974 on Marriage, the Child Protection Law, and the Compilation of Islamic Law (KHI) have regulated the protection of children after divorce based on the principle of the best interests of the child. However, the implementation of these provisions still faces several challenges, such as non-compliance with maintenance obligations and prolonged disputes over custody rights. This study employs a normative legal method to analyse the effectiveness of post-divorce child protection regulations and the various challenges in their implementation. It is hoped that the findings of this study will provide more effective policy recommendations to ensure the well-being of children after their parents' divorce.